2005
DOI: 10.1097/01.fjc.0000159046.35241.4e
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of the Effect of Nicotine on Kir6.1 Channels by Superoxide Anion Production

Abstract: KATP channels are a complex of regulatory sulfonylurea receptor subunits and the pore-forming inward rectifiers such as Kir6.1. Using the whole-cell patch-clamp technique, we investigated the interaction of nicotine with the Kir6.1 subunit as well as the underlying mechanism. Stable expression of Kir6.1 in HEK-293 cells yielded a detectable inward rectifier KATP current. This inward current was significantly inhibited by PNU-37883A and by a specific anti-Kir6.1 antibody. Nicotine at 30 and 100 microM increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Recent studies of stably expressed Kir6.1 in HEK-293 cells (in the absence of any SUR subunit) revealed that co-application of hypoxanthine and xanthine oxidase produced a significant increase in Kir6.1 currents that could be abolished by tempol. 27 Thus, superoxide or other ROS might act directly on Kir6.1 to increase the contribution of K ATP channels to afferent arteriolar tone during T1D. Such a scenario might also contribute to the exaggerated impact of Ba 2+ -sensitive Kir2.1 channels on afferent arteriolar tone during diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of stably expressed Kir6.1 in HEK-293 cells (in the absence of any SUR subunit) revealed that co-application of hypoxanthine and xanthine oxidase produced a significant increase in Kir6.1 currents that could be abolished by tempol. 27 Thus, superoxide or other ROS might act directly on Kir6.1 to increase the contribution of K ATP channels to afferent arteriolar tone during T1D. Such a scenario might also contribute to the exaggerated impact of Ba 2+ -sensitive Kir2.1 channels on afferent arteriolar tone during diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have implicated tempol in the regulation of the K ATP channel (Kir6.1) (Hanna et al, 2005). Superoxide enhanced K ATP channel activity in guinea pig cardiac myocytes yet decreased the K ATP channel opening probability in cerebral vessels (Liu and Gutterman, 2002; Gebremedhin et al, 2008).…”
Section: Mechanistic Basis Of the Blood Pressure-lowering Effect mentioning
confidence: 99%
“…Tempol may have activated K ATP channels on sympathetic neurons in this preparation because the blunting of the hypotensive action of intravenous tempol by glibenclamide was diminished in SHR pretreated with the ganglion blocking drug, hexamethonium (Chen et al, 2007a). Activation of K ATP channels also can generate ROS that were blocked by tempol (Hanna et al, 2005). …”
Section: Mechanistic Basis Of the Blood Pressure-lowering Effect mentioning
confidence: 99%
“…Hence this response may be due to the activation of nicotinic receptors expressed on the endothelial cells of cutaneous blood vessels (Hagforsen et al 2002) Finally, nicotine may activate K ATP channels through increasing superoxide production as demonstrated under in vitro conditions (Hanna et al 2005). …”
Section: Cutaneous Vasodilationmentioning
confidence: 99%